Coping with COVID-19: Measuring self-efficacy, collective efficacy and proxy efficacy beliefs - Silva,Andrêze (2023)
Abstract Investigating efficacy beliefs for coping with COVID-19 can be helpful when proposing interventions that contribute to mitigate the disease. Six scales of efficacy beliefs for coping with COVID-19 were built: self-efficacy; family and community collective efficacy; and proxy efficacy to the municipal, state and federal governments. To obtain evidence of validity based on the internal structure and reliability estimates of these measures, 518 participants completed an online form. Exploratory factor analysis revealed that all scales had a unidimensional structure. Cronbach's alphas ranged from .819 to .968. Although positive correlations predominated between the scores of the six scales, the magnitudes were, in general, weak or moderate, showing that they were distinct constructs. These scores differed from each other, with levels of efficacy decreasing as individual control over the actions necessary to mitigate COVID-19 decreased. Thus, the six scales initially presented satisfactory psychometric properties. Study-related limitations, implications and recommendations are also presented.